Proteomic characterization of pediatric craniopharyngioma intracystic fluid by LC‐MS top‐down/bottom‐up integrated approaches. Issue 15 (20th June 2014) - Martelli, Claudia; Iavarone, Federica; Vincenzoni, Federica; Rossetti, Diana Valeria; D'Angelo, Luca; Tamburrini, Gianpiero; Caldarelli, Massimo; Di Rocco, Concezio; Messana, Irene; Castagnola, Massimo; Desiderio, Claudia; Guttman, Andras
<x xml:space="preserve">Abstract</x> The combination of top‐down and bottom‐up platforms was utilized for the LC‐MS proteomic characterization of the intracystic fluid of adamantinomatous craniopharyngioma pediatric brain tumor disease. Proteins and peptides characterization was achieved by high‐resolution LC‐ESI‐LTQ‐Orbitrap‐MS analysis while low‐resolution LC‐ESI‐IT‐MS was applied for the complete screening of the samples and the evaluation of the protein distribution within patients. Top‐down analyses were applied to liquid/liquid extracted samples while bottom‐up analyses were performed after trypsin digestion of both untreated and pretreated samples. The two proteomic approaches were complementary for the characterization of the proteome of craniopharyngioma intracystic fluid. Proteins and peptides involved in inflammation, mineralization processes and lipid transport were identified, in agreement with the calcium flecks, cholesterol granules and bone residues characteristic of this fluid. Apolipoprotein A‐I, A‐II, C‐I and J, hemoglobin fragments, ubiquitin, α‐2‐HS‐glycoprotein or fetuin A, α‐1‐antichymotrypsin, vitamin D binding protein, and α‐1‐acid glycoprotein were characterized. These data could be relevant for the comprehension of the processes involved in the pathogenesis of the disease and the development of the cyst and could contribute to the individuation of therapeutic targets for the reduction of the cyst volume delaying and/or avoiding invasive surgical treatments.